Italian Chimeras Narrating Italy through the Writing of Sebastiano Vassalli - Gordon, Robert S.c.; Gordon, Robert S.c.; Tulante, Meriel (Peter Lang, 2020)
Sebastiano Vassalli (1941?2015) engaged in an ambitious project to narrate Italy, the nation, its people and its pathologies. His vast cast of characters includes a prototypical fascist father, a terrorist son, a Carmelite nun, Virgil and other literary giants, Francesco Crispi, and an orphan girl burnt as a witch. His historical panorama delves into memory, regional geographies, and national identity to interrogate the condition of the Italian nation since World War II. For Vassalli, chimeras are the myths or illusions that have repeatedly ensnared the nation, resulting in the national, social, and geopolitical dysfunctions that he denounces. Despite his literary successes and prizes (the Campiello Prize for his career, shortlisting for the Nobel Prize for Literature), he remains isolated on the Italian literary scene. This absence of critical attention largely stems from his combative relationship with the literary establishment, which developed after he broke with the neoavantgarde of the 1960s and was reinforced by his accusatory stance toward contemporary society. This book represents the first study of Vassalli's works as a whole, investigating this difficult, contradictory, yet highly accomplished intellectual who was a major commentator on postwar society and a strongly original voice in Italian literature.